Ensemble-Based Virtual Screening of Mycobacterium tuberculosis ClpC1 Inhibitors - Tayyab, Hafsa; Ridzwan, Nor FW; Mohamad, Saharuddin B (Archives of Clinical and Biomedical Research, 2022)
Tuberculosis (TB) is an airborne transmissible disease caused by Mycobacterium tuberculosis (Mtb), responsible for 1.3 million deaths annually. Due to increased cases of drug resistance to Mtb, a new treatment regime for TB needs to be discovered. ClpC1 plays a crucial role in the protein homeostasis of Mtb thus, presents as a promising target in controlling TB infection. The present study aimed to identify potential inhibitors for the ClpC1 N-terminal domain (ClpC1-NTD) by applying the relaxed complex scheme in virtual screening that accounts for the target and ligand flexibility. A filtered library of natural product compounds was virtually screened against each of the selected ClpC1-NTD dominant conformations from the ensemble generated using molecular dynamics simulation. The promising compounds with the strong binding affinity to ClpC1 protein were then further analysed for their molecular interactions. The stability of the most potent compound was examined through a complex MD simulation while the pharmacokinetics properties were gathered using SwissADME and pkCSM. The results showed that ligand NP132 formed a strong and stable complex with good pharmacokinetics and toxicological profile.